Autoparametric Resonance Systems for Vibration-Based Energy Harvesters. (November 2015) - Kurmann, L; Hoffmann, D; Folkmer, B; Manoli, Y; Woias, P; Anderegg, R
Abstract: Motivation for this paper is the creation of a new kind of (vibration) kinetic energy harvester systems that can effectively transfer environmental mechanical vibrations into electrical energy over a wider frequency bandwidth than conventional devices. This paper presents a potential improvement in the 1DoF vibration transducer class and examining therefore analytically the behavior of such systems using strong nonlinear springs. Then a new 2DoF class of vibration transducer is presented having a strong nonlinear characteristic which is well suited for autoparametric resonance vibrations.